CALON PRESIDEN PERSEORANGAN SEBAGAI PERWUJUDAN ASPIRASI RAKYAT PADA PROSES DEMOKRATISASI DI INDONESIA - Parlindungan Sitorus (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractPolitical discourse that is being discussed today is Provincial Assembly of the Republic ofIndonesia proposes the fifth amendment of Contitution 1945 that candidates of Presidentand Vice President can be from individual candidate; by offering amendment of paragraph6A article (2) Constitution 1945 to become â€œCandidate of President and Vice Presidentcome from the proposal of political party of general election participant or from individualâ€.This discourse actually based on idea to realize democratization in the practice ofpresidential election; that sovereignty is on the peopleâ€™s hand and to provide the maximumspace for the people who has capability to lead this great nation; and basically all people isequal in front of Law and Governance. Provincial Assembly believes that that proposal iscompatible with democracy principle that related to recognition on peopleâ€™s right to electand to be elected even without having any political party.Keywords: Individual candidate, People aspiration, Democratization, â€œDeparpolisasiâ€